Pengembangan E-Modul Berbasis Inkuiri Terbimbing untuk Melatihkan Keterampilan Berpikir Kritis Peserta Didik pada Materi Laju Reaksi - Salsabila Rachmasari Putri Putri; Sukarmin (PendIPA Journal of Science Education, 2023)
This research was conducted with the aim of producing appropriate guided inquiry-based e-modules to train students' critical thinking skills on the subject of reaction rates. Feasibility is reviewed based on validity, practicality, and effectiveness. This research used the Research and Development (R&D) method by Sugiyono to the product trial stage. Product trials were carried out on a limited basis with 15 class XI students at SMA Negeri 12 Surabaya. The following details the research results obtained, namely (1) the e-module validation results get mode 4 so that they are included in the good/valid category, (2) the average results of student response questionnaires get a percentage of 95% so that it is said to be very practical and the average results the average observation of student activity gets a percentage of 97% so it is said to be very practical, and (3) the posttest results for each component of critical thinking skills get a percentage of â‰¥ 81% so it is said to be very effective and the average n-gain score obtained is 0.86 which is included in the high category so that it can be said to be effective. Based on the results of the research obtained, it shows that guided inquiry-based e-modules are feasible for training students' critical thinking skills in the matter of reaction rates.